Electrochemically exfoliated functionalized graphene flakes: facile synthesis, 3rd order optical nonlinearity and optical limiting response - Abu Bakar, Mohamad Aizat; Danial, Wan Hazman; Norhisham, Noriliya Aina; Abdul Majid, Zaiton; Ibrahim, Abdul Razak; Mat Jafri, Mohd Zubir; Ahmad, Fauzan; Abdullah, Mundzir (Elsevier, 2022)
High quality graphene production is prerequisite for good performance in nonlinear optics application such as fast optical communications, all-optical switching, and optical limiting. Graphene journey begins with the method of synthesizing graphene which need to be simple, fast, and environmentally friendly. Hence, we introduce the method by exfoliating graphite by electrochemical route to produce good quality functionalized graphene for various nonlinear optics application. In this work, functionalized graphene flakes are synthesis by using two different electrodes; furnaced graphite rod (Gr-FG) and non-furnaced graphite electrode (Gr-NFG). Visual inspection on the synthesized Gr-FG and Gr-NFG show dark murky color solutions give the impression of high yield functionalized graphene flakes. Further observation under transmission electron microscopy (TEM), selected area electron diffraction (SAED), and UV–vis and Raman analysis confirm the good quality functionalized graphene structure. The nonlinear optical behavior of the functionalized graphene was accessed via Z-scan technique with 637 nm laser source operating in continuous mode with simultaneous monitoring of the close and open aperture signal. Close aperture profile of Gr-FG and Gr-NFG display nonlinear refraction, whereas open aperture profile shows reverse saturable absorption (RSA). Equation fitting reveals higher n2 magnitude for Gr-FG compared to Gr-NFG, but the later possess higher magnitude of β. Further analysis on the 3rd order of optical nonlinearity by z-scan technique reveal the admirable value at the range of 10−6 esu. Optical limiting performance conducted via transmittance-based measurement shows superior limiting of Gr-NFG compared to Gr-FG.